Analisis Perilaku Penggunaan Teknologi Informasi (Studi pada Dosen Universitas Pattimura Ambon) - Wairisal, Lambertus P; Khusniyah, Nur (Universitas Brawijaya, Indonesia, 2012)
This research is to analyze the influence of organization culture, perceived ease of use of information technology, perceived usefulness of information technology and behavioral intention to use informationtechnology toward behavior usefulness of information technology by lecturer at Pattimura University- Ambon. Sample are 277 people and the sample determination uses probability sampling method with the simple technique of random sampling. Data analysis techniques in this research employs factor analysis and path analysis. The analysis result proves that at Pattimura University, organization culture which has significant influence towards perceived usefulness in information technology, organization culture hassignificant influence towards perceived usefulness in information technology and organization culture has significant influence towards behavioral intention to use information technology. Perceived ease of use information technology significantly, influences perceived usefulness, perceived usefulness in information technology significantly, influence intention to use information technology, perceived usefulness in information technology significantly influences intention to use information technology and intention of usinginformation technology significantly influences useful behavior of information technology.